A 40-month multicentre, randomised placebo-controlled study to assess the efficacy and carry-over effect of repeated intra-articular injections of hyaluronic acid in knee osteoarthritis: the AMELIA project. Issue 11 (17th August 2011) - Navarro-Sarabia, F; Coronel, P; Collantes, E; Navarro, F J; de la Serna, A Rodriguez; Naranjo, A; Gimeno, M; Herrero-Beaumont, G
Abstract : Objective: AMELIA (OsteoArthritis Modifying Effects of Long-term Intra-articular Adant) was designed to compare against placebo the efficacy and safety of repeated injections of hyaluronic acid (HA) and its effect on disease progression over 40 months. Methods: A multicentre, randomised, patient and evaluator-blinded, controlled study in 306 patients fulfilling American College of Rheumatology criteria for knee osteoarthritis, radiological grades II–III (Kellgren–Lawrence) and joint space width ≥2 mm. Patients received four cycles of five intra-articular HA or placebo injections with a follow-up of 6 months after the first and second cycles, and 1 year after the third and fourth cycles. Osteoarthritis Research Society International (OARSI) 2004 responder criteria were used to assess efficacy. The consumption of rescue medication was a secondary outcome. Adverse events were recorded for safety purposes. Results: At the 40-month visit significantly more patients responded to HA compared with placebo (OARSI 2004, p=0.004). The number of responders to HA increased through the study, whereas those to placebo did not change. Significant differences were also found in favour of HA for each individual component of the OARSI 2004. No safety problems were recorded. Conclusions: The results of AMELIA offer pioneer evidence that repeated cycles of intra-articular injections of HA not only improve knee osteoarthritis symptoms during the in-between cycle period but also exert a marked carry-over effect for at least 1 year after the last cycle. In this respect, it is not possible to establish if this carry-over effect reflects true osteoarthritis remission or just a modification of the disease's natural course. ClinicalTrials.gov number, NCT00669032